Nile : urban histories on the banks of a river - AlSayyad, Nezar (Edinburgh University Press, 2019)
Narrates the history of cities that appeared and disappeared on the banks of the river Nile over four millennia. The Nile, the world's longest river system, has figured prominently in historic events over millennia. This book views the Nile as both the stage on which these events occurred and as an actor in its unfolding history. It explores the intersection of natural forces and human intervention to take readers on a series of historical journeys along the river, from its sources to the Mediterranean Sea. Each chapter focuses on a particular historical period and the cities, events, important figures and the encounters between groups and cultures that shaped it. -- Publisher.